The Concept of Maslahah in the Dynamics of the Rukyah and Hisab Methods for Determining the Beginning of the Lunar Month - Karis Lusdianto (Istinbath : Jurnal Hukum, 2023)
Determining the beginning of the lunar month is a significant issue in Islamic tradition, especially in establishing the timing of religious observances such as Ramadan and Eid al-Fitr. The methods used for this determination, namely rukyah (moon sighting) and hisab (astronomical calculation), often lead to differing opinions among Muslims. This paper aims to analyze the dynamics between the rukyah and hisab methods through the lens of the maslahah theory, which emphasizes the achievement of good and the prevention of harm for the community. The analysis shows that the rukyah method is more relevant for determining the beginning of months related to major religious observances, as it aligns with sharia tradition and helps maintain the unity of the Muslim community. Conversely, the hisab method is more efficient for determining the start of months not directly related to religious observances, such as 1 Muharram, as it provides certainty and ease in planning. The conclusion of this paper is that integrating both methods, with an emphasis on their respective contexts, can optimize the maslahah for Muslims, ensure the smooth execution of religious practices, and support unity within the community.